Characterization of Crystalline Structure and Thermostability of Debranched Chickpea Starch-Lauric Acid Complexes Prepared Under Different Complexation Conditions - Wongprayoon, Suchitra; Tran, Thierry; Gibert, Olivier; Dubreucq, Eric; Piyachomkwan, Kuakoon; Sriroth, Klanarong (Chiang Mai University, 2018)
Chickpea starch was debranched with pullulanase, then complexed with lauric acid (LA) using two starch concentrations (3 and 10% w/w), two starch/LA mole ratios (1:0.1 and 1:1 mol anhydroglucose unit/mol LA) and two complexation temperatures (60 and 95 oC). Different conditions influenced the formation, crystalline structure, morphology and thermostability of the complexes. Complexation occurred under the same conditions, and in competition with, retrogradation. Lower starch concentration favored the formation of complexes. At 3% starch concentration, complexation at 60 oC produced more complexes, but with lower thermostability (Tp 96 oC) and smaller crystallite sizes (4.78-4.83 nm), compared to complexes obtained at 95 oC (111-117oC, 13.18-14.31 nm) that exhibited a highly crystalline torus/disc spherulitic morphology. These results confirm that the properties of starch-fatty acid complexes can be tailored to meet specific application requirements, by adjusting both the completed debranching and complexation conditions.